Lost in the maze [videorecording (DVD)] - Camargo, Milton; Englehart, Denis; Kirsch, Curt (BMG Global, 2025)
Lost in the Maze is a gripping true story of two men navigating the Uraricoera River in the Amazon jungle. Their journey takes a harrowing turn when their boat capsizes in wild rapids, leaving them stranded in one of Earth's most remote and unforgiving regions.